“URBAN ISLAND” AS AN ENERGY ASSESSMENT TOOL. THE CASE OF MOUZAIA, AL ALGERIA - Boukarta, Soufiane; Berezowska-Azzag, Ewa (Journal of Applied Engineering Science, 2017)
Residential buildings in Algeria are responsible for 41% of total country’s energy consumption. In this study, a holistic approach has been adopted to analyze the building stock of a middle-sized city (Mouzaia) in Algeria according to their energy consumption. The purpose of this paper is to test the pertinence of the urban island scale as an energy assessment tool. This study is based on a statistical approach of the islands’ typologies to single out a model able to estimate the energy load of a simple dwelling or for an island according to a set of indicators. Thus, Urban islands were clustered according to their geometrical and physical attributes that considers a large panel of indicators such as island’s area, built-up area, compactness, porosity, land use, areal density, built density, solar admittance and the passive volume. The conclusion of this analysis shows the classification profiles of the building stock of Mouzaia according to their energy consumption with an accuracy level of 86%. Also, this model developed can be implemented to a GIS tool in order to identify within a large scale the different scenarios which could be adopted to reduce the energy load of dwellings.
Keywords: Algeria; sensitivity analysis; existing buildings; urban islands; typology; energy use